Coaching Parents to Implement Trial-Based Functional Analysis via Telehealth - Kiyak, Uzeyir Emre; Saral, Dincer; Olcay, Seray (Specijalna edukacija i rehabilitacija, 2024)
Introduction. The procedure of trial-based functional analysis implemented by parents has the potential to determine the purpose of problematic behaviors. A telehealth strategy may be less expensive, it takes less time, and provides more families with access to treatments. As a result, it could be a good alternative for families as poor access to resources and knowledge may worsen problem behaviors. Objectives. The purpose of this study was to evaluate the ability of mothers to conduct a trial-based functional analysis at home, with training and coaching via telehealth. Methodes. Three mothers aged between 32 and 54 and their children between 18 and 26 years participated in the study. The study employed a multiple baseline design across behaviors to examine the effectiveness of behavioral skill training and coaching through telehealth on the accurate use of trial-based functional analysis conditions by mothers of children with developmental disabilities. Results. Results showed that mother participants conducted each condition of trial-based functional analysis with 100% accuracy. Moreover, the mothers had positive opinions regarding the study. Conclusion. In conclusion, this study provided support for parent involvement in the assessment of their children with developmental disabilities.
Keywords: trial-based functional analysis; problem behavior; developmental disabilities; telehealth; coaching